Guidelines for the Development of Urban Design through Fulfilling Professional Role - Horayangkura, Vimolsiddhi (Journal of Architectural/Planning Research and Studies (JARS), 2017)
In the past decades, urban design as a profession has radically uplifted the livability of world cities which have been under accelerated urbanization. Through critically examining document and observation of urban environmental phenomena in the attempt to analyse the urban design practice in Thailand, which has been under the professional control of Architect Council Thailand, it was found that the urban design professional role has not been well defined as well as not having been comprehensive, taking into account the general coverage of international urban design essences. More specifically, the dimension of urban connectivity and the provision of facility to serve human movement / urban mobility in daily life have been excluded as well as the design for sustainability – social, economic and environmental – has to be sufficiently addressed. It is postulated that if the professional control would be significantly modified to enchance practices according to the international concern standards, it would provide measures to increase the livability of such rapidly urbanized cities as Bangkok and other major cities. The betterment would promisingly become the basis for launching Thailand 4.0, and be in accordance with urban planning and development missions of public sector under the 2017 Constitution of Thai Kingdom.